Diagnostic performance of the RT-qPCR method targeting 85B mRNA in the diagnosis of pulmonary Mycobacterium tuberculosis infection - Mehmet Demirci; Suat Saribas; Nigar Ozer; Sezer Toprak; Emel Caglar; Gonenc Ortakoylu; Pelin Yuksel; Gulsel Ayaz; Hrisi B. Tokman; Omer Uysal; Harika O. Dinc; Tevhide Ziver; et al. (Elsevier, 2018)
Background: Several nucleic acid amplification techniques (IS6110, 16S rRNA, and 85B mRNA) were developed for the rapid, direct detection of Mycobacterium tuberculosis. We aimed to assess the diagnostic performance of 85B mRNA-based RT-qPCR by comparing with the real-time PCR COBAS TaqMan MTB Kit while using the BACTEC MGIT 960 method as the gold standard. Methods: 60 patients with confirmed pulmonary TB and 60 individuals without TB were included as the study and control groups, respectively. Sputum specimens were cultured using LJ and BACTEC MGIT 960 systems. Extracted DNA was used for COBAS PCR in a CONAS TaqMan 48 analyzer. 85B mRNA detection was performed by RT-qPCR. Results: The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of COBAS TaqMan MTB Test were detected as 93.3%, 83.3%, 84.8%, 92.6%, and 88.3%, respectively. The same diagnostic parameters of RT-qPCR were: 98.3%, 95.0%, 95.2%, 98.3%, and 96.7%, respectively. According to the binary logistic regression analysis, RT-qPCR (OR: 19,924, p < 0.001) was identified as the more optimal test. Conclusion: RT-qPCR targeting the 85B gene of M. tuberculosis seems to be a more useful and rapid technique than DNA-based methods for detecting live M. tuberculosis bacilli from sputum specimens. Keywords: 85B mRNA, Mycobacterium tuberculosis, RT-qPCR, BACTEC MGIT 960